Avaliação clínica e laboratorial de cães com linfoma cutâneo tratados com lomustina - Duarte, Amanda Resende [UNESP]; Marques, Jéssica de Assis [UNESP]; Zahn, Fabíola Soares [UNESP]; Machado, Luiz Henrique de Araújo [UNESP] (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2016)
The aim of this prospective study was to evaluate the clinical response of dogs with cutaneous lymphoma treated with lomustine (CCNU) and to identify possible adverse effects and toxicity during treatment. Fifteen dogs, seven females and eight males aged between five and 17 years old, diagnosed with cutaneous lymphoma by histopathological analysis were selected and treated with lomustine at 90 mg/m2 every three weeks. Monitoring was carried out and consisted of the assessment of laboratory hematology and serum chemistry before and during treatment. Partial response was observed in 53.3% of the animals. None of the animals achieved a complete response and seven dogs (46.6%) had progressive disease. The median survival time was 22 days. The major hematological and biochemical changes found after therapy were leukopenia (73.3%), thrombocytopenia (60%) and anemia (46.1%). Renal and liver toxicity was observed in 40% and 73.3% of dogs, respectively. Hematocrit, total protein, leukocyte count, neutrophil count, serum creatinine, ALT, GGT, alkaline phosphatase and urine specific gravity were affected during therapy. The use of lomustine as a monotherapy in the treatment of canine cutaneous lymphoma was effective; however, adverse effects occurred and compromised the quality of life of the majority of dogs in this study. Therefore, lower doses of lomustine should be considered in future studies.
Clinical and laboratorial evaluation of dogs with cutaneous lymphoma treated with lomustine
Keywords: Adverse effects; CCNU; Cutaneous lymphoma; Dogs; Oncology